A Multicenter Experience With the Placement of Self-Expanding Metallic Tracheobronchial Y Stents. Issue 1 (January 2016) - Madan, Karan; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Mohan, Anant; Mehta, Ravindra; Pattabhiraman, Vallandramam; Goyal, Rajiv; Agarwal, Ritesh
Abstract : Background: Deployment of a bifurcation (Y) stent is often required in patients with airway obstruction or fistulization near the tracheal carina. Herein, we describe our experience with placement of self-expanding metallic Y stents. Methods: This was a retrospective analysis of data of consecutive subjects who underwent placement of self-expanding metallic Y stent over 2 years at 6 different centers. We describe the technique, complications, and outcomes of metallic Y stent placement at the tracheal carina. Results: Thirty-eight subjects (25 men) with a mean age of 54.8 years underwent Y stent placement. The most common underlying disease was carcinoma of the esophagus (65.8%). The most common indication for stent insertion was central airway obstruction in 30 (78.9%) subjects followed by airway-esophageal fistula. Respiratory failure was present in 17 (44.7%) subjects at admission. The Y stent was deployed using either the rigid (n=32) or the flexible (n=6) bronchoscope, and was successfully placed in 37 of the 38 (97.4%) subjects. There was rapid improvement in symptoms and subsequent resolution of respiratory failure after stent placement. There was no periprocedural mortality and few stent-related complications. On follow-up at 12 weeks, 18 patients had died due to progression of the underlying disease. Conclusion: The insertion of a metallic Y stent results in immediate palliation of malignant airway obstruction or airway fistulization near the tracheal carina with rapid improvement of symptoms. Abstract : Supplemental Digital Content is available in the text.